"Tell me, how bright your hypomania is, and I tell you, if you are happily in love!"—Among young adults in love, bright side hypomania is related to reduced depression and anxiety, and better sleep quality. (March 2015) - Brand, Serge; Foell, Stephan; Bajoghli, Hafez; Keshavarzi, Zahra; Kalak, Nadeem; Gerber, Markus; Schmidt, Norman B.; Norton, Peter J.; Holsboer-Trachsler, Edith
Abstract Background. Studies on adolescents and adults show that romantic love (RL) is associated with favorable emotional states. However, data on these associations are scarce for adults. The aim of the present study was, therefore, to explore the associations between RL, symptoms of depression, anxiety, hypomania (bright side and dark side), and sleep in a sample of adults. Method. A total of 844 participants currently in love (M = 24.79 years, 75.8% females) took part in the study. They completed a series of questionnaires related to RL, symptoms of depression, anxiety, hypomania (bright side and dark side), and sleep. Results. An increased state of RL was associated both with the bright and the dark side of hypomania (BRHYP and DAHYP). Relative to participants with BRHYP, participants with DAHYP reported stronger symptoms of depression and state anxiety, and poor sleep quality. Conclusions. The pattern of results adds to our knowledge that in adults RL is not entirely a joyful and happy period of life. Rather, data suggest that for young adults in love, bright versus dark side of hypomania was associated with a different quality of psychological functioning and sleep. We conclude that experiencing RL might be a critical life event associated with symptoms of depression and anxiety, and poor sleep.